Open Science, Excellent Science! EC policies and initiatives in support of open science - Tsoukala, Victoria (Septentrio Conference Series, 2018)
Watch the VIDEO. Victoria will focus on discussing existing EC policies and recent policy developments designed to support open science across Europe. She will present the current open access policy and the plans of the Commission for open science in Horizon Europe, the revised Recommendation on access to and preservation of scientific information and research data in the proposed revision of the PSI directive. She will discuss Plan S and its possible implementation in the context of the current and future FP requirements, the initiative of the EC for an open access publishing platform and the launch of the European Open Science Cloud.